Effect of Web-Based Linear Program Teaching Material Use on Student’s Learning Result in Linear Program Material. (Study on SMK 6 Kota Malang) - Elina Nur Fatimah (Pancaran Pendidikan, 2018)
Utilization of learning website / e-learning as one of the teaching materials is expected to improve the effectiveness and the efficiency of learning, so that will make the students’ learning result became maximum. The improvement of learning result by utilizing the learning website can make the students learn according to their own paces. So, in this research the researcher aims to examine the effect of web-based linear program teaching material use on students’ learning result in linear program material. This study used experimental research with quasi experiment design which divided into 2 classes, that was the control class which used the classical method and the experimental class which used the web media. The subjects of the research were students of XI A class and XI B class which had 20 students for both classes. The data collecting technique used a test then it would be analyzed by using independent t-test sample. The results showed that there were some differences in learning result between the control group and the experimental group where the experimental group which used the learning website had a higher post-test average score than the control group. This showed that there was a positive and significant impact of website utilization on students’ learning result.